B chromosomes and Robertsonian fusions of Dichroplus pratensis (Acrididae): intraspecific support for the centromeric drive theory - Bidau, Claudio Juan (2004)
We tested the centromeric drive theory of karyotypic evolution in the grasshopper Dichroplus pratensis, which is simultaneously polymorphic for eight Robertsonian fusions and two classes of B chromosomes. A logistic regression analysis performed on 53 natural populations from Argentina revealed that B chromosomes are more probably found in populations with a higher proportion of acrocentric chromosomes, as the theory predicts. Furthermore, frequencies of B-carrying individuals are significantly negatively correlated with the mean frequency of different Robertsonian fusions per individual. No significant correlations between presence/absence or frequency of Bs, and latitude or altitude of the sampled populations, were found. We thus provide the first intraspecific evidence supporting the centromeric drive theory in relation to the establishment of B chromosomes in natural populations.